A Meta-analysis of Randomized Control Trials: The Impact of Vitamin C Supplementation on Serum CRP and Serum hs-CRP Concentrations - Jafarnejad, Sadegh; Boccardi, Virginia; Hosseini, Banafshe; Taghizadeh, Mohsen; Hamedifard, Zahra (Current Pharmaceutical Design, 2018)
Objective: The present meta-analysis was designed to assess the effects of vitamin C supplementation on serum C-reactive Protein (CRP) levels. Methods: We conducted a comprehensive systematic search of the literature in Scopus, PubMed and Google Scholar until May 2018. The pooled Weighted Mean Difference (WMD) and its 95% Confidence Interval (CI) in baseline and at the end of the trial were calculated to assess the net change in serum CRP by using random-effects model. The heterogeneity was assessed by I2 test. Combined and stratified analyses were used in the metaanalysis. Results: From 306 articles found and screened in our initial search, 12 studies were included with 446 participants in supplementation groups and 447 in control groups. The pooled effect size analysis showed a significant reducing effect of vitamin C supplementation on circulating CRP level (−0.23 mg/L, 95% CI, −0.44, -0.03, p=0.02), with a significant heterogeneity effect across the studies involved. Subgroup analyses showed that vitamin C supplementation significantly lowered CRP among trials. The most significant effect was found 1) on hs- CRP as the representative inflammatory marker (-0.43 mg/L, 95% CI -0.76, -0.1) 2) in subjects with a baseline CRP≥3 (-1.48 mg/L, 95% CI -2.84, -0.11) 3) in subjects under <60 years old of age (-0.23 mg/L, 95% CI -0.44,- 0.01) 4) or using intravenous administration of vitamin C (-0.89 mg/L, 95% CI -1.49,-0.3). Conclusion: The present meta-analysis shows that vitamin C supplementation reduces serum CRP level, particularly in younger subjects, with higher CRP baseline level, at a lower dosage and intravenous administration.
Keywords: C-reactive protein